Advanced DVR with Zero-Sequence Voltage Component and Voltage Harmonic Elimination for Three-Phase Three-Wire Distribution Systems - Margo P; Mauridhi Heri Purnomo; Mochamad Ashari; Zaenal P; Takashi Hiyama (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
Dynamic Voltage Restorer (DVR) is a power electronics device to protect sensitive load when voltage sag occurs. Commonly, sensitive loads are electronic-based devices which generate harmonics. The magnitude and phase of compensated voltage in DVR depend on grounding system and type of fault. If the system is floating, the zero sequence components do not appear on the load side. Meanwhile, in a neutral grounded system, voltage sag is extremely affected by zero sequence components. A blocking transformer is commonly installed in series with DVR to reduce the effect of zero sequence components. This paper proposes a new DVR control scheme that is capable of eliminating the blocking transformer and reducing harmonic distortion. The system uses fuzzy polar controller to replace the conventional PI or FL controller that is commonly used. By taking into account the zero sequence components in the controller design, the effects of zero sequence components can be compensated. Simulated results show the effectiveness of the proposed DVR controller